PENGARUH DIMENSI LOCUS OF CONTROL TERHADAP STRES KERJA PADA KARYAWAN PERANTAU - I Gusti Ayu Mirah Eka Putri; Komang Rahayu Indrawati (CV. ADIBA AISHA AMIRA, 2025)
The limited availability of employment opportunities has led to intense competition within society, prompting individuals to seek solutions through migration to other cities. One of the main challenges faced by migrant workers is work stress, which can be caused by excessive workloads that individuals are unable to manage effectively. This study aims to examine the effect of locus of control on the level of work stress among migrant employees. The research employed a quantitative approach with a survey design, in which data were collected through an online questionnaire that had been tested for validity and reliability. A simple linear regression analysis revealed a very strong and significant relationship between locus of control and work stress (R = 0.760; R² = 0.578), with the regression equation Y = 26.682 + 0.327X. These results indicate that each one-unit increase in locus of control contributes to a 0.327-unit increase in work stress. This finding supports the theory that individuals’ perceptions of control over their lives influence their psychological burden in adapting to new work environments.